The Glue Joint Strength of Laminated Timber Decking made from Three Malaysian Hardwood Species - Sahri, Mohd Hamami (1984)
Glue joint strengths of laminated timber decking made from three Malaysian hardwood species i.e. Kempas (Koompassia malaccensis), Nemesu (Shorea pauciflora) and Seraya (Shorea curtisii) were evaluated. Single and mixed species laminations were produced using a phenolresorcinol formaldehyde adhesive at room temperature. Shear block tests were performed according to the ANSI/ASTM D 905-49(76) specification. All specimens except one exhibited high glueline shear strength values with each combination, exceeding the minimum industrial requirements of 5515 kilopascal (kPa) and 4137 kilopascal (kPa) for dry and wet specimens, respectively. A comparison between laboratory and factory-made assemblies and various factors affecting the glueline shear strength of these assemblies are discussed.